A NOTE ON ZOOPLANKTON DISTRIBUTIONS AT TWO DIFFERENT TYPES OF WATER MANAGEMENT SYSTEMS IN THE MUDA RICE AGROECOSYSTEM - Amir Shah Ruddin Md Shah; Ismail Sahid; Mashhor Mansor; Othman Russ (Tropical Life Sciences Research, 2008)
The species composition and abundance of the zooplankton community from two types of irrigation water management system (recycled and uncontrolled flow) in the Muda agro-ecosystem, were studied over two during rice planting seasons during the period of 2002–2003. A total of 25 species of rotifers, 19 species of cladocerans and 2 species of copepods were identified during the study period. There was not much difference in the number of taxa between the two areas (recycled and uncontrolled flow). Copepods were the most dominant group followed by the rotifers and cladocerans for both plots systems studied, respectively. The most common species recorded from both areas were Simocephalus latirostris and Diaphanosoma sarsi (cladocerans), and followed by Asplanchna pridonta and Platyias patulus (rotifers). Komposisi dan kelimpahan komuniti zooplankton di dalam dua sistem pengurusan air (kitar semula dan mengalir) di agroekosistem Muda telah dikaji selama dua musim penanaman padi pada tahun 2002–2003. Sejumlah 25 spesies rotifer, 19 spesies kladosera dan 2 spesies kopepoda telah berjaya dikenal pasti dalam kajian ini. Tidak ada perbezaan yang ketara bagi bilangan taksa zooplankton di antara dua sistem pengurusan air (kitar semula dan mengalir). Kelimpahan kumpulan kopepoda adalah dominan diikuti oleh kumpulan rotifera dan akhir sekali kladosera untuk kedua-dua plot yang dikaji. Spesies kladosera yang kerap direkodkan di kedua-dua sistem pengairan ini adalah Simocephalus latirostris dan Diaphanosoma sarsi manakala untuk rotifera ialah Asplanchna pridonta dan Platyias patulus.